Cognitive Behaviour Therapy Reduce Online Gaming Addiction in the Senior High School Students - Febriana Sartika Sari; Irna Kartina; Heni Nur Kusumawati; S. Dwi Sulisetyawati (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Online gaming addiction is a world phenomena which take interest. There has been a significant increase in the number of empirical studies examining various aspects of problematic online gaming addiction. Online gaming addiction causes bad effect in the physical health, anxiety and sleeplessness. One of the attempt to reduce online gaming addiction is cognitive behavior therapy. The study aimed to identify the effect of Cognitive Behaviour Therapy to online gaming addiction. The study used quasy experiment design without control group. The study used online gaming addiction questionnaire which was valid and reliable to measure students online gaming addiction. There were four sessions of Cognitive Behaviour Therapy were given to the respondents. The sample of the study were 30 students of senior high school who were taken by purposive sampling technique. The data were analized using paired t test. The study indicated that the mean score of online gaming addiction reduced after 4 sessions of Cognitive Behaviour Therapy. The mean score of online gaming addiction was 57,17 before intervention and 43,23 after intervention. The statictical analysis showed that there was significant effect of Cognitive Behaviour Therapy to reduce online gaming addiction. (p value < 0,05). The conclusion was Cognitive Behaviour Therapy can reduce online gaming addiction.